Ancient languages as a simulation environment - Nadia Petrucci (Firenze University Press, 2019)
The combination of ancient languages and new technologies has always represented a stimulating oxymoron in didactic reflections: nowadays, the question is not really whether technologies are useful to learn ancient languages, but whether these disciplines can help to acquire the proper mindsets to prepare the conscious, productive and ethical use of technologies as envisaged by the definition of digital skills made in Lisbon. To this end, we examine the specific tool of simulation, since the disciplines of antiquity were indeed a privileged simulation environment a long time before the adoption of digital technology, inspiring the creation of virtual microworlds to express metaphors of reality and sometimes even utopias quite distinct from the real world. The purpose of this paper is to re-establish a coplanar relationship between knowledge of the ancient world and the digital skills that are necessary to design and explore virtual microworlds. Such a relationship aims to train our students in the skills that are likely to be necessary for their personal fulfilment beyond the constraints of their chosen study course. Le lingue antiche come ambiente di simulazione L'accostamento fra lingue antiche e nuove tecnologie ha sempre rappresentato un ossimoro stimolante nella riflessione didattica: oggi però non dobbiamo chiederci se le tecnologie siano utili all'apprendimento delle lingue antiche, ma se queste discipline siano idonee a realizzare schemi mentali che predispongano all'uso consapevole, produttivo ed etico delle tecnologie previsto dalla definizione delle competenze digitali di Lisbona. Esaminiamo a questo scopo lo strumento specifico della simulazione, perché le discipline dell'antichità costituiscono un ambiente di simulazione privilegiato già da tempi lontanissimi dal digitale, ispirando la creazione di micromondi virtuali per esprimere metafore della realtà e talora perfino utopie distinte dal mondo reale. Lo scopo del presente contributo è ristabilire un rapporto complanare fra la conoscenza del mondo antico e le competenze digitali necessarie alla progettazione ed esplorazione di micromondi virtuali, che abbia come scopo la formazione dei nostri studenti di oggi, oltre i limiti dell'indirizzo di studi scelto, in vista delle probabili competenze necessarie alla loro realizzazione personale.